Konektor Masker Hijab - satriadi, Satriadi; Husain, Muh. Saleh; Wiharja, Muh. Kurniawan Adikusuma (Universitas Negeri Makassar, 2021)
The partner of this community partnership program is the Islamic Knowledge Group of the Babussalam Mosque, Tirta Mas Complex, Makassar. The problems is: (1) The activities carried out by the Babussalam Taqlim Assembly group are recitation, Maulid, Isra' Mi'raj, and social gatherings, (2) There are no training activities that are easy and can directly have a selling value in Islamic Knowledge Group of the Babussalam Mosque, and (3) Lack of knowledge and insight in being creative to produce hijab mask connectors. The goal is the ability to make hijab connectors independently with various forms of variation. The methods used are lectures, demonstrations, discussions, questions and answers, and companion partners. The results achieved are (1) partners know about making hijab mask connectors, (2) partners have skills in designing hijab mask connectors with various variations, (3) Increase partner productivity during a pandemic to make hijab mask connectors